Exploiting cellophane birefringence to generate radially and azimuthally polarised vector beams. (4th February 2015) - Kalwe, Johnston; Neugebauer, Martin; Ominde, Calvine; Leuchs, Gerd; Rurimo, Geoffrey; Banzer, Peter
Abstract: We exploit the birefringence of cellophane to convert a linearly polarised Gaussian beam into either a radially or azimuthally polarised beam. For that, we fabricated a low-cost polarisation mask consisting of four segments of cellophane. The fast axis of each segment is oriented appropriately in order to rotate the polarisation of the incident linearly polarised beam as desired. To ensure the correct operation of the polarisation mask, we tested the polarisation state of the generated beam by measuring the spatial distribution of the Stokes parameters. Such a device is very cost efficient and allows for the generation of cylindrical vector beams of high quality.